IMPLEMENTASI STRATEGI GURU DALAM PENGEMBANGAN PENDIDIKAN KARAKTER PADA KURIKULUM MERDEKA - Erlina Timbul; Rozana, Kardiana Metha; Fitriyah, Siti Ni’matul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe teacher strategies in developing character values in second-grade students through the Independent Curriculum, analyze the implementation of character value development in learning activities and school habituation, and identify supporting factors and obstacles faced by teachers. This research is motivated by the urgency of developing character values in elementary school students in facing behavioral problems and increasingly complex student backgrounds. Strengthening character education is essential in shaping students’ personalities to behave according to norms in school and society. This study uses a qualitative approach with a case study conducted at SDN Merjosari 1 Malang City. Data collection techniques include interviews, observation, and documentation involving second-grade teachers, students, and supporting teachers. The results show that teacher strategies are implemented through integrating character values into learning, teacher role modeling, and consistent habituation of positive activities in the school environment. Character development is carried out through intracurricular and extracurricular activities that internalize discipline, responsibility, cooperation, and honesty. Supporting factors include a conducive school environment, supportive policies, and collaboration among teachers. Obstacles include differences in student character, limited awareness among some students, and external environmental influences. Improvement efforts involve strengthening collaboration between schools and parents and reinforcing continuous habituation programs to support optimal and sustainable character development. Therefore, this study is expected to contribute practically and theoretically to character education in elementary schools in Indonesia, particularly in enhancing effective character education practices, improving student behavior outcomes, and supporting sustainable educational development across diverse learning environments.